As aventuras de Huckleberry Finn: análise da tendência de normalização em corpus paralelo a partir das traduções de Monteiro Lobato e de José Roberto O‘Shea - Fumagalli, Leandra Aparecida (2022)
This study investigates the occurrence of one of the translation-related phenomena known as normalization. In general, normalization refers to the tendency to exaggerate features and conform to standards, which are characteristics of both the source text and the culture. Baker (1993/1996) described this phenomenon, which was later expanded upon by Maria Nélia Scott in 1998. Scott proposes eleven normalization features, seven of which were chosen for the current study analysis: differences in text/sentence length, differences in aspects of punctuation, register shift, omission and/or addition, differences in aspects of syntactically complex structures, shift in less common words and other translation changes. Thus, to develop this research and seek normalization features, we compiled a parallel corpus composed of Mark Twain's Adventures of Huckleberry Finn (1885) and its translations by Monteiro Lobato (1934) and by José Roberto O'Shea (2019) to Portuguese, that is two different time periods. The data for the analysis used are related to the sensitive epithet nigger, which has prejudiced content. Furthermore, we used the computer program WordSmith Tools version 8.0 and the tools it provides to search for such data. In general, Corpus based Translation Studies reflections from Corpus Linguistics enables the analysis and identification of normalization evidences. As a result, we conclude that the term nigger appears more frequently in O'Shea's translation (195 occurrences, singular and plural) than in Lobato's translation (166 occurrences, singular and plural), despite the fact that the occurrence of this word is lower in both versions when compared to Twain's Adventures of Huckleberry Finn (212 occurrences, singular and plural). In terms of normalization, the most noticeable featuresin Lobato's translation were omission and/or addition, differences in text/sentence length, register shift (from colloquial to formal) and change in complex structures, whereas in O'Shea's translation register shift, omission and/or addition, differences in aspects of punctuation and differences in text/sentence length are the most commonly used